Social and political challenges in the regulation of mycotoxin contamination - Bandyopadhyay, Ranajit; Williams, J.H.; Ojiambo, P. (2007)
Mycotoxins are toxic to humans and animals when present in food and feed above tolerance limits. Reduction in mycotoxin exposure of humans and animals has necessitated regulatory interventions by some national governments and international agencies. Conservative estimates of lost crop revenues, and the cost of research and monitoring activities, range from $0.5 to $1.5 billion annually. To achieve current global regulatory compliance in mycotoxin safety levels farmers also have to spend more effort and assume higher risk. Regulatory levels vary between countries and, as a result, mycotoxins act as Technical Banier to Trade and have led to trade disputes between nations. While food production, processing and marketing systems of developed economies have been largely successful in delivering mycotoxin safe products, regulations have been ineffective in most less-developed countries due to socio-economic, technical, institutional and policy factors.Agricultural products of the best quality are exported from less developed countries to augment export earnings, leaving poorer quality foods to be consumed locally, compromising the health of local populations. Wherever regulations cannot be implemented the key management options for consumers and farmers are awareness and adoption of simple mycotoxin management practices.